PENGARUH KARAKTERISTIK PERUSAHAAN DAN KARAKTER EKSEKUTIF TERHADAP TAX AVOIDANCE STUDI PADA PERUSAHAAN JASA SUB SEKTOR REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2012-2016 - ULFI JEFRI; NURBAETI .; SURACHMAN . (JURNAL ILMIAH KOHESI, 2020)
Taxes as one source of state acceptance is a burden for every taxpayer (body or individual) including the company's realestate sector and property. To minimize the payment of such tax, the company conducts tax evasion action. The method inthis research is a quantitative method with a secondary data type obtained from the annual financial report of IDX(www.idx.co.id) The population in this study, namely all the companies in the real estate sector and the property listed on theIndonesia Stock Exchange period 2012-2016. Based on T test results can be concluded (1) the size of the company affectstax evasion (2) Leverage has no effect on tax evasion, (3) Sales growth does not affect tax evasion (4) The risk of acompany affecting tax evasion. And the test is the company size, leverage, sales growth and risk of the company influencejointly – equal to tax evasion.